Effects of dietary concentrated mannan oligosaccharides supplementation on growth, gut mucosal immune system and liver lipid metabolism of European sea bass (Dicentrarchus labrax) juveniles. Issue 2 (February 2015) - Torrecillas, Silvia; Montero, Daniel; Caballero, Maria José; Robaina, Lidia; Zamorano, Maria Jesús; Sweetman, John; Izquierdo, Marisol
Abstract The study assesses the effects of dietary concentrated mannan oligosaccharides (cMOS) on fish performance, biochemical composition, tissue fatty acid profiles, liver and posterior gut morphology and gen expression of selected parameters involved on the intestinal immune response and liver lipid metabolism of European sea bass (Dicentrarchus labrax). For that purpose, specimens of 20 g were fed during 8 weeks at 0 and 1.6 g kg−1 dietary cMOS of inclusion in a commercial sea bass diet. Dietary cMOS enhanced fish length, specific and relative growth without affecting tissue proximate composition. However, cMOS supplementation altered especially liver and muscle fatty acid profiles by reducing levels of those fatty acids that are preferential substrates for β-oxidation in spite of a preferential retention of long chain polyunsaturated fatty acids (LC-PUFA), such as 20:4n-6 or 22:5n-6, in relation to the down-regulation of delta 6/5 desaturase gene expression found in liver. Besides, dietary cMOS supplementation reduced posterior gut intestinal folds width and induced changes on the gene expression level of certain immune-related genes mainly by down regulating transforming growth factor β (TGFβ) and up-regulating immunoglobulin (Ig), major histocompatibility complex class II (MHCII), T cell receptor β (TCRβ) and Caspase 3 (Casp-3). Thus, dietary cMOS inclusion at 0.16% promoted European sea bass specific growth rate and length, stimulated selected cellular GALT-associated parameters and affected lipid metabolism in muscle and liver pointing to a higher LC-PUFA accumulation and promoted β-oxidation.